The art of classroom observation: The Case of Quirino State University and Can Tho University - Liriolyn Pacursa; Eduard Alip; Thi Phuong Thao Do; Chi Tham Trinh (CTU Journal of Innovation and Sustainable Development)
Classroom observation is a professional development model that helps lecturers gain a lot of experience in teaching effectively through cooperation, but it needs to be done in a reasonable way. The purpose of this study is to investigate the advantages and disadvantages of classroom observation and the strategies used by lecturers at College of Teacher Education (CTE), Quirino State University - Maddela Area the Philippines and School of Education (SoE), Can Tho University, Viet Nam used, correlated to the age, teaching experience, and education level of the respondents and to see whether there are any significant differences in the two cultures. The researchers used a descriptive type of design in the study, with a survey as the primary instrument for the data gathering. Using a quota sampling technique, 40 lecturers participated in the study. Based on the findings of the study, the majority of faculty members of CTE underwent classroom observation once per semester, whereas the majority of lecturers at SoE underwent classroom observation twice per semester. Moreover, the advantages of classroom observations outweigh the disadvantages as perceived by respondents. This finding provided evidence that both institutions implemented classroom observation for their lecturers. This simultaneously encourages lecturers to reflect and develop self-awareness about their practice and provides evidence of actual teacher performance, their strengths, and their areas for improvement. Thus, applicable recommendations for professional and organizational growth were made based on the found specific challenges to foster a collaborative environment favorable to improving teaching quality.